From farms to foreign markets: Assessing India’s banana export performance and trade direction (2014-2024) - Sathya, K N; Uma, K; Malarkodi, M; Vidhyavathi, A; Anandhi, V; Kavitha , M (Plant Science Today, 2025)
The banana (Musa sp.) is one of the most traded commodities on the international market and a significant commercial fruit crop, ranking above mango in trade volume. Globally, banana ranks first in production but third in cultivated area. In India Andhra Pradesh leads in banana area, production and productivity followed by Maharashtra and Tamil Nadu. The study aims to evaluate the export performance and instability index of bananas for the past ten years (2014-2024). It also forecasts the export trends in the upcoming years. The study is based on secondary data collected from the official websites for the period 2014-2024. Statistical tools such as Markov Chain analysis, Instability Index (II), Revealed Comparative Advantage (RCA), Revealed Symmetric Comparative Advantage (RSCA), Trade Specialization Index (TSI) and Nominal Protection Coefficient (NPC) were used to analyze the data. The result revealed that from the transition probability matrix, the UAE was the most stable importer and retained 100 % of its market share. Iraq retained 42.63 % of its imports, while 57.37 % shifted to the UAE, indicating trade diversification where, Iran had lost its market share entirely, with 41.92 % redirected to "Others," suggesting an unstable trade environment. The II categorized Iran (70.18 %), Iraq (31.97 %) and Saudi Arabia (39.09 %) as high-risk markets, while Oman (14.21 %) and the UAE (28.32 %) demonstrated relatively stable trade patterns. However, a strong recovery was observed in 2024, with an RCA of 1.31 and a positive RSCA value, reflecting enhanced global positioning. The TSI remained consistently close to positive throughout the decade, indicating India’s specialization and status as a net exporter with minimal banana imports. The NPC showed a declining gap between domestic and international prices from 50.93 % in 2014 to 33.64 % in 2024, suggesting increased competitiveness and better returns for Indian farmers in global markets.